Rupture of a caesarean scar ectopic pregnancy: A case report - Harrison L. Odgers; Rebecca A.M. Taylor; Jananie Balendran; Christopher Benness; Joanne Ludlow (Elsevier, 2019)
Background: Caesarean scar pregnancy is an uncommon form of ectopic pregnancy characterized by implantation into the site of a caesarean scar. Common clinical features include vaginal bleeding and abdominal pain; however, a significant proportion of cases are asymptomatic. The primary diagnostic modality is transvaginal ultrasound. There is no current consensus on best-practice management. Case presentation: A 36-year-old woman, G7P2, presented to an early-pregnancy service with vaginal spotting and an ultrasound scan demonstrating a live caesarean scar ectopic pregnancy at 8 + 5 weeks' gestation. On examination she was hemodynamically stable with a soft abdomen. She was advised to have dilation and curettage (D&C) under ultrasound guidance; however, she was concerned that she might require more extensive surgery, such as a hysterectomy and so requested non-surgical management. On day 1 she underwent ultrasound-guided embryocide with lignocaine followed by inpatient multi-dose systemic methotrexate. Her beta-human gonadotrophic hormone level decreased. Repeat ultrasound on day 18 demonstrated a persistent caesarean scar ectopic pregnancy with increased vascularity, and so uterine artery embolization (UAE) was performed with a view to D&C the following day. This plan was altered to expectant management with ongoing follow-up by a different clinician who had had previous success with UAE alone. On day 35 the patient presented with life-threatening vaginal bleeding that required an emergency total abdominal hysterectomy. Conclusions: Caesarean scar pregnancies are uncommon. Multiple treatment strategies have been employed, with variable degrees of success. Further research into risk stratification and management are needed to guide clinician and patient decision making. Keywords: Caesarean ectopic, Caesarean scar pregnancy, Ectopic pregnancy, Ruptured ectopic pregnancy